Effectiveness of advance care planning with family carers in dementia nursing homes: A paired cluster randomized controlled trial. (March 2018) - Brazil, Kevin; Carter, Gillian; Cardwell, Chris; Clarke, Mike; Hudson, Peter; Froggatt, Katherine; McLaughlin, Dorry; Passmore, Peter; Kernohan, W George
Background: In dementia care, a large number of treatment decisions are made by family carers on behalf of their family member who lacks decisional capacity; advance care planning can support such carers in the decision-making of care goals. However, given the relative importance of advance care planning in dementia care, the prevalence of advance care planning in dementia care is poor. Aim: To evaluate the effectiveness of advance care planning with family carers in dementia care homes. Design: Paired cluster randomized controlled trial. The intervention comprised a trained facilitator, family education, family meetings, documentation of advance care planning decisions and intervention orientation for general practitioners and nursing home staff. Setting/participants: A total of 24 nursing homes with a dementia nursing category located in Northern Ireland, United Kingdom. Family carers of nursing home residents classified as having dementia and judged as not having decisional capacity to participate in advance care planning discussions. Results: The primary outcome was family carer uncertainty in decision-making about the care of the resident (Decisional Conflict Scale). There was evidence of a reduction in total Decisional Conflict Scale score in the intervention group compared with the usual care group (−10.5, 95% confidence interval: −16.4 to −4.7; p < 0.001). Conclusion: Advance care planning was effective in reducing family carer uncertainty in decision-making concerning the care of their family member and improving perceptions of quality of care in nursing homes. Given the global significance of dementia, the implications for clinicians and policy makers include them recognizing the importance of family carer education and improving communication between family carers and formal care providers.